Development of ITC E- Choupal Based Rural Financial Inclusion Model - Sharma, Shikha; Sharma, Sanjeev K. (Indian Journal of Finance, 2017)
It wouldn't be wrong if one says that India lives in villages. More than 70% of Indian citizens are located in rural areas. For India's economy to be strong, the rural India needs to grow. Financial inclusion is a crucial driver for such growth by providing the financial products/services and information to large sections of society and ICT (information and communication technologies) has an imperative role to play. Usage of ICT in rural financial arena would help in attaining the goal of financial inclusion at an affordable timely and efficient manner. Various ICT based interventions/models have been initiated by RBI and a number of financial institutions in the industry. But there is lack of financial intervention that has been co-created in conjunction with local farmers/ people. Inspired by the success of one of such co- developed participatory model in rural procurement and marketing infrastructure that is popularly known as E-Choupal, we attempted to replicate the experience in the financial sector. The study conceptualized an E-Choupal RuralÂ Financial Intervention Model with an aim to deliver financial products/services and information by leveraging ITC's E-Choupal network that must be tested for feasibility, efficiency, and sustainability. The proposed rural financial inclusion model would use the E-Choupal and Choupal Sagar networks to increase admittance to various financial products/services and information in the intervention areas. The proposed ICT - enabled innovative rural financial solution might facilitate intriguing the banking services to unbanked farmers/poor people in far - flung rural areas.